Body Mass Index, Physical Activity Habits and Physical Function Contribute to Fatigue in the Rest Home Residents. Issue 4 (7th August 2020) - Acaröz Candan, Sevim
ABSTRACT: Backgrounds: Fatigue is a common complaint in older adults living in rest homes. The aim of this study was to investigate the factors associated with fatigue among older adults living in a rest home. Methods: This cross-sectional study was carried out with a total of 92 older adults. Fatigue was evaluated by the Fatigue Severity Scale (FSS). The sociodemographic characteristics, quadriceps and handgrip strength, functional capacity and physical function were assessed using a structured questionnaire, digital dynamometers, 6-minute walking test and Short Physical Performance Battery, respectively. Results: The prevalence of fatigue was 67.4%. FSS showed significant correlations with age, female gender, body mass index, physical activity habits, quadriceps strength, handgrip strength, functional exercise capacity, and physical function. However, in the regression analysis, only body mass index, physical activity habits and physical function were responsible for 51% of the variance in fatigue among rest home residents. Physical activity habits and physical function were the best predictors of fatigue explaining 47.5% of variance. Conclusion: This study demonstrated that body mass index, physical activity habits and physical function contributed to fatigue in rest home residents. These factors can be used to identify individuals at high risk of fatigue and to attenuate fatigue levels.